1986
DOI: 10.1161/01.str.17.5.913
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler measurement of middle cerebral artery blood flow velocity: a validation study.

Abstract: SUMMARY Measurement of intracranial arterial blood flow velocity is a new technique with potentially a number of very useful applications. This study validates the technique by comparing it to cerebral blood flow (CBF) measured using intravenous Xenon and extracranial clearance recording. We have measured the middle cerebral artery (MCA) blood flow velocity in 17 symptomatic patients with the EME TC 264 transcranlal Doppler velocimeter and compared these measurements to the ipsilateral hemispheric cerebral blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
373
4
2

Year Published

1990
1990
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 752 publications
(394 citation statements)
references
References 14 publications
15
373
4
2
Order By: Relevance
“…16,21 Significant correlations between mean blood velocity in the middle cerebral artery and cerebral blood flow at rest in healthy subjects has been published by several authors. [22][23][24] This correlation, however, could not be substantiated by other investigations. 25 There is no data regarding these features in patients with liver diseases.…”
Section: Discussioncontrasting
confidence: 59%
“…16,21 Significant correlations between mean blood velocity in the middle cerebral artery and cerebral blood flow at rest in healthy subjects has been published by several authors. [22][23][24] This correlation, however, could not be substantiated by other investigations. 25 There is no data regarding these features in patients with liver diseases.…”
Section: Discussioncontrasting
confidence: 59%
“…28 During cardiopulmonary bypass and in patients with cerebrovascular diseases, correlations between CBF and V MCA values are rather weak with wide betweenpatient variation. 14,29 In a number of previous studies, relative changes in CBF were reflected by changes in V MCA in a proportional manner, suggesting that MCA diameter remains constant. 30 Nevertheless, other investigations could show that illness and interventions as orthostasis, migraine attacks, CO 2 -rebreathing, or vasoactive medicine could change the MCA diameters by 5% to 12%.…”
Section: Discussionmentioning
confidence: 95%
“…However, studies measuring 133 Xe clearance and radioactive microspheres have shown that relative changes in CBFV correlate well with changes in cerebral blood flow. 21,22 TCD sonography is now widely used as a surrogate measure of cerebral blood flow. 23 Interpatient variability in CBFV measurements can be due to variations in Doppler probe positioning, resulting in different angles of insonation (i.e., the angle at which the Doppler beam impacts on the artery).…”
Section: Objectifmentioning
confidence: 99%